Pan American Crohn's and Colitis Organization (PANCCO) and the Interamerican Society of Endoscopy (SIED) consensus on endoscopy in inflammatory bowel disease - Parra-Izquierdo, Viviana (2024)
Introduction: Endoscopy plays a fundamental role in inflammatory bowel disease (IBD), and becomes essential in diagnosis, treatment monitoring, and detection and management of complications. Materials and methods: The Pan American Crohn's and Colitis Organization (PANCCO) and the Inter-American Society of Endoscopy (SIED) appointed 22 Latin American experts in IBD to develop a consensus study using the modified Delphi method, based on the best available evidence. A working group of 22 members from 9 countries identified 15 topics and formulated 98 statements, who participated in 2 rounds of voting. It was defined as agreement of ≥80% of experts for each statement. Results: After the voting of all the statements, 8 statements were obtained that did not reach 80% consensus among the participants, so the questions were reconsidered in the Coordinating Committee of the consensus with the participation of the expert reviewers of these questions and 7 final statements were voted again by all the experts in a second round and 1 was eliminated with consensus. After two rounds of voting, the experts reached consensus with literature review with the best available evidence, the most important issues were developed with scientific evidence supporting each of the statements around the topic of endoscopy in IBD. Conclusions: Consensus statements were developed and based on the best available evidence about endoscopy in inflammatory bowel disease.